2020
DOI: 10.1038/s41598-020-61936-w
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression, characterization, and quantification in human cancer cell lines of the Anaplastic Large-Cell Lymphoma-characteristic NPM-ALK fusion protein

Abstract: Systemic anaplastic large cell lymphoma (ALcL) is an aggressive t-cell lymphoma most commonly seen in children and young adults. The majority of pediatric ALCLs are associated with the t(2;5)(p23;q35) translocation which fuses the Anaplastic Lymphoma Kinase (ALK) gene with the nucleophosmin (npM) gene. the npM-ALK fusion protein is a constitutively-active tyrosine kinase, and plays a major role in tumor pathogenesis. In an effort to advance novel diagnostic approaches and the understanding of the function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…It was previously reported that MS99 degrades the nucleophosmin (NPM)−anaplastic lymphoma kinase (ALK) fusion protein. 52 Because Karpas 299 cells overexpress NPM-ALK, 65 normal Karpas 299 (n-Karpas 299) and senescent Karpas 299 (s-Karpas 299) cells were employed to evaluate the degradation ability of Gal-MS99. The results demonstrate that Gal-MS99 does not promote degradation of NPM-ALK in n-Karpas 299 cells even at a concentration of 1 μM (Figure 4B), while in s-Karpas 299 cells, this protein is degraded by both MS99 and Gal-MS99 (Figure 4C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was previously reported that MS99 degrades the nucleophosmin (NPM)−anaplastic lymphoma kinase (ALK) fusion protein. 52 Because Karpas 299 cells overexpress NPM-ALK, 65 normal Karpas 299 (n-Karpas 299) and senescent Karpas 299 (s-Karpas 299) cells were employed to evaluate the degradation ability of Gal-MS99. The results demonstrate that Gal-MS99 does not promote degradation of NPM-ALK in n-Karpas 299 cells even at a concentration of 1 μM (Figure 4B), while in s-Karpas 299 cells, this protein is degraded by both MS99 and Gal-MS99 (Figure 4C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Inactivation of tumor suppressors and activation of proto-oncogenes are secondary to mutations, deletions, or chromosomal translocations [ 128 , 129 , 130 ]. The main translocations implicated in the genesis of lymphomas are t(14;18)(q32;q21), associated with follicular lymphoma (FL) and diffuse large B-cell lymphoma (DLBCL) [ 131 , 132 ]; t(8;14)(q24;q32), that is found in Burkitt lymphoma (BL) [ 133 ]; t(2;5)(p23;q35), typical of some T/NK-derived anaplastic large cell lymphomas [ 134 ]; and t(11;14)(q13;q32), described in many cases of mantle cell lymphoma (MCL) [ 135 , 136 ].…”
Section: Introductionmentioning
confidence: 99%